Targeted apoptotic immune modulator for the treatment of metastatic EGFR-positive solid tumors - Derrick Broka; Shoshana Klein; Alexei Shir; Babette Schade; Meera Saxena; Athanasia Dasargyri; Anita Jarzebinska; Caroline De Feyter; Davor Bajic; David Colecchia; Lucia D'Amico; Eric Kitas; et al. (Proceedings of the National Academy of Sciences, 2025)
Aberrant activation and overexpression of the epidermal growth factor receptor (EGFR) occurs in various solid cancers and often correlates with poor outcome. The clinical benefit from EGFR-targeted therapies is usually short-lived, with resistance being driven by tumor heterogeneity and an immunosuppressive tumor microenvironment (TME). To address these limitations, we developed Targeted Apoptotic Immune Modulators (TAIM), a nonviral nanoparticle platform for the targeted delivery of polyinosine:polycytosine (polyIC), to simultaneously induce tumor cell death and activate antitumor immunity. The first TAIM compound, TAR001, was designed as a systemic treatment against metastatic EGFR-positive solid cancers. Here, we present TAR001’s multifaceted mode of action. We demonstrate that TAR001 is selective toward EGFR-overexpressing cancers, provoking a pattern recognition response, apoptosis, cytokine secretion, and antitumor immunity. TAR001 modulates the TME, recruiting and activating both innate and adaptive immune cells. Systemic delivery of TAR001 markedly extends survival and inhibits tumor growth in multiple murine tumor models. TAR001 represents an innovative, safe, multimodal treatment approach with the potential to benefit patients with metastatic head and neck, non–small cell lung cancer, colorectal, renal, and triple-negative breast cancers. This unique modality utilizes a broad range of mechanisms to overcome the tumor’s ability to escape apoptosis and immune cell activation.